Axial and radial CO concentration profiles in an atmospheric bubbling FB combustor - Tarelho, Luís António da Cruz (2005)
Atmospheric Bubbling Fluidised Bed Combustion (ABFBC) of a bituminous coal and anthracite with particle diameters in the range 500– 4000 mm was investigated in a pilot-plant facility (circular section with 0.25 m internal diameter and 3 m height). The experiments were conducted at steady-state conditions using three excess air levels (10, 25 and 50%) and bed temperatures in the 750–900 8C range. Combustion air was staged, with primary air accounting for 100, 80 and 60% of total combustion air. The effect of limestone addition was also tested. Large CO concentrations were observed inside the bed, up to 8 and 6% (v/v) in the cases of anthracite and bituminous coals, respectively. These concentrations decreased sharply as the gases emerged from the bed, and the CO flue gas concentration observed was in general less than 2000 and 4000 ppm, respectively. The CO flue gas concentration increased with air staging and with limestone addition, but decreased with either excess air or temperature increase. The observed results confirm the influence of sand particles (and probably of SO2) in the ‘quenching’ of the oxygenated free radicals (HO and HO2) reactions responsible for the CO oxidation inside the bed.